2006
DOI: 10.1111/j.1365-2672.2006.03181.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plant density and microbial composition on water quality from a free water surface constructed wetland

Abstract: Aims:  To correlate microbial community composition and water quality changes within wetland cells containing varying plant densities and composition in a free water surface (FWS) constructed wetland. Methods and Results:  Water chemistry was monitored weekly for nitrate, orthophosphate, and suspended solids, at various sites throughout the wetland for 6 months. Treatment ponds with 50% plant cover had about a 96·3% nitrate removal. The average change between the influent and effluent was 50–60% nitrate remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 39 publications
3
50
0
1
Order By: Relevance
“…Ibekwe et al (14) also observed an abundance of Betaproteobacteria in the soil and rhizosphere of a wetland. These authors suggest that Alphaproteobacteria and Betaproteobacteria may be important in such systems for the degradation of organic matter (14,16). The prevalence of fungal groups and Alphaproteobacteria and Betaproteobacteria in vernal pools suggests that microbial communities are rich in heterotrophic organisms.…”
Section: Vol 74 2008 Microbial Community Patterns Of Vernal Pools 2555mentioning
confidence: 99%
“…Ibekwe et al (14) also observed an abundance of Betaproteobacteria in the soil and rhizosphere of a wetland. These authors suggest that Alphaproteobacteria and Betaproteobacteria may be important in such systems for the degradation of organic matter (14,16). The prevalence of fungal groups and Alphaproteobacteria and Betaproteobacteria in vernal pools suggests that microbial communities are rich in heterotrophic organisms.…”
Section: Vol 74 2008 Microbial Community Patterns Of Vernal Pools 2555mentioning
confidence: 99%
“…In many laboratories, utilization of commercial kits for DNA isolation is also frequent. Among them are MoBIO PowerSoil DNA kit (MoBIO) [19,24,62], ultra clean soil DNA kit (Ozyme, MoBIO) [5,61,99], and fast DNA spin kit for soil (BIO 101/Q-Biogene) [29,50,55,102].…”
Section: Other Extraction and Purification Methodsmentioning
confidence: 99%
“…In vegetated treatment wetlands, the density and type of plants affect microbial community dynamics (Ibekwe et al, 2006;Calheiros et al, 2009) by providing labile forms of organic carbon, surfaces for biofilm growth, and oxygen gradients (Reddy and D'Angelo, 1997). The ability of decaying plants to create anoxic zones in surface and subsurface flow constructed wetlands is important for the transformation of trace organic contaminants, because some compounds are more readily transformed under aerobic conditions (e.g., ibuprofen) while others (e.g., tonalide and galaxolide) are more readily transformed under anaerobic conditions (Hijosa-Valsero et al, 2010).…”
Section: Jasper Et Almentioning
confidence: 99%